Understanding important variables for mode preference; A Case study of intercity land mode - Roza, A. (2021)
This study aims to describe factors that influenced the mode preference for intercity land movement in Malaysia. Bus and train as intercity land public transport service was observed during the construction of the ETS (Electric Train Service) project in Malaysia. This study adopted a qualitative research study using the Revealed Preferenced data and crosstabs procedure. The reliability test has been used over 17 questionnaire items to measure the consistency of the questionnaire. The result indicated that the overall reliability of the questionnaire is reliable. To evaluate the adequacy of the sample size, the factor analysis had conducted. The Kaiser-Meyer-Olkin (KMO) and Bartlett's test value is significant, which measures verified the sampling adequacy for the sample analysis. This research highlighted that the variable of fare, travel time, mode accessibility, departure frequency, and mode availability are some important attributes that influenced bus user preference for intercity land movement. Learning a lesson from the KL- Ipoh corridor, the completion of the ETS double-tracking project is predicted to affect the bus mode's ridership in the KL - Penang corridor. This finding can be beneficial for setting future strategy on particular intercity modal goals. © Published under licence by IOP Publishing Ltd.